2020
DOI: 10.1186/s12931-020-01576-w
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopist's perception of the quality of the single-use bronchoscope (Ambu aScope4™) in selected bronchoscopies: a multicenter study in 21 Spanish pulmonology services

Abstract: Background The disposable bronchoscope is an excellent alternative to face the problem of SARS-CoV-2 and other cross infections, but the bronchoscopist's perception of its quality has not been evaluated. Methods To evaluate the quality of the Ambu-aScope4 disposable bronchoscope, we carried out a cross-sectional study in 21 Spanish pulmonology services. We use a standardized questionnaire completed by the bronchoscopists at the end of each bronchos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In a non-ICU setting where in general procedures other than lavage are also performed, data are very limited. The only study we could identify was a prospective Spanish multi-centre study of 300 patients using the AMBU ® aScope 4 [12]. Thirty-six bronchoscopists participated, and most procedures were lavages or washings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a non-ICU setting where in general procedures other than lavage are also performed, data are very limited. The only study we could identify was a prospective Spanish multi-centre study of 300 patients using the AMBU ® aScope 4 [12]. Thirty-six bronchoscopists participated, and most procedures were lavages or washings.…”
Section: Discussionmentioning
confidence: 99%
“…Portability, ease of use, and the lack of requirement of cleaning staff are among the advantages of SUFBs over reusable scopes that are important in a pandemic situation [11]. Indeed, it could be argued that the uptake of SUFBs has out-paced research in these devices with only one publication of experience in a bronchoscopy suite [12]. Clearly, bronchoscopic procedures and indications differ between the ICU and endoscopy location.…”
Section: Introductionmentioning
confidence: 99%
“…When a lesion is close to the lung and hilum, especially an endobronchial lesion, fibreoptic bronchoscopy biopsy and brush examination are preferred; however, when a lesion is close to the outer lung and chest wall, performing fibreoptic bronchoscopy is difficult ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are satisfaction surveys or bench model testing. For example, a user satisfaction study in Spain showed that one of the newest SUFB models received high ratings for ease of use, imaging, and suction [ 89 ]. In a simulation study, a slim model of a SUFB required more time for nasal intubation than a RFB.…”
Section: Comparative Trials Of Sufbs and Rfbsmentioning
confidence: 99%